OCRFinder: a noise-tolerance machine learning method for accurately estimating open chromatin regions - Ren, Jiayi; Liu, Yuqian; Zhu, Xiaoyan; Wang, Xuwen; Li, Yifei; Liu, Yuxin; Hu, Wenqing; Zhang, Xuanping; Wang, Jiayin (Frontiers in Genetics, 2023)
Open chromatin regions (OCRs) are the genomic regions associated with basic cellular physiological activities, while the chromatin accessibility is reported to affect gene expressions and functions. A basic computational problem is to efficiently estimate open chromatin regions, which could facilitate both genomic and epigenetic studies. Currently, ATAC-seq and cfDNA-seq (plasma cell-free DNA sequencing) are two popular strategies to detect OCRs. As cfDNA-seq can obtain more biomarkers in one round of sequencing, it is considered more effective and convenient. However, in processing cfDNA-seq data, due to the dynamically variable chromatin accessibility, it is quite difficult to obtain the training data with pure OCRs or non-OCRs, and leads to noise problem for either feature-based approaches or learning-based approaches. In this paper, we propose a learning-based OCR estimation approach with noise-tolerance design. The proposed approach, named OCRFinder, incorporates the ideas of ensemble learning framework and semi-supervised strategy to avoid potential overfitting of noisy labels, which are the false positives on OCRs and non-OCRs. Compared to different noise control strategies and the state-of-the-art approaches, OCRFinder achieved higher accuracies and sensitivities in the experiments. In addition, OCRFinder also has excellent performance in ATAC-seq or DNase-seq comparison experiments.